2016
DOI: 10.1074/jbc.m116.734053
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Membrane-bound Prepore Species Clarifies the Lytic Mechanism of Actinoporins

Abstract: Pore-forming toxins (PFTs) are cytolytic proteins belonging to the molecular warfare apparatus of living organisms. The assembly of the functional transmembrane pore requires several intermediate steps ranging from a water-soluble monomeric species to the multimeric ensemble inserted in the cell membrane. The non-lytic oligomeric intermediate known as prepore plays an essential role in the mechanism of insertion of the class of β-PFTs. However, in the class of α-PFTs, like the actinoporins produced by sea anem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 56 publications
0
26
1
Order By: Relevance
“…55 The dimer interface obtained by Tanaka et al 8 is been described as the basis for the octameric pore observed in the FraC structure and, more recently, for an octameric prepore structure of this toxin. 25 However, from our results and previous published data, 16 we cannot rule out the possibility that this dimeric interface can nucleate up to 8 units by the sequential addition of single or dimeric units to complete a final ring-like assembly. EqtII was described to be organized in the cell surface as a mixture of oligomeric species mostly including those formed by even number of units.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…55 The dimer interface obtained by Tanaka et al 8 is been described as the basis for the octameric pore observed in the FraC structure and, more recently, for an octameric prepore structure of this toxin. 25 However, from our results and previous published data, 16 we cannot rule out the possibility that this dimeric interface can nucleate up to 8 units by the sequential addition of single or dimeric units to complete a final ring-like assembly. EqtII was described to be organized in the cell surface as a mixture of oligomeric species mostly including those formed by even number of units.…”
Section: Discussioncontrasting
confidence: 62%
“…Moreover, it would be possible that different intermediate oligomeric states could form arc‐like toroidal pores with one edge filled by protein complexes and the other with bend lipids, similar to those observed in the MACPF/CDC protein superfamily or for the Bcl2 protein Bax . Further studies should confirm this hypothesis since current high quality data obtained by electron microscopy or atomic force microscopy at high protein concentration do not support the formation of arc‐like structures in the mechanism of action of actinoporins …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The monomeric units then oligomerize to form pores in which the N-terminal α-helix lines the channel walls in conjunction with lipids (Tanaka et al 2015). Some studies suggest the relevance of protein-protein interactions (Mechaly et al 2011;Tanaka et al 2015;Morante et al 2016), while others assume that there is no need for such protein interfaces to stabilize oligomeric intermediates for the final pore assembly (Mancheno et al 2003(Mancheno et al , 2006). …”
Section: Computational Insights Into the Mechanism Of Actinoporin Pormentioning
confidence: 99%